The Role of AI-Powered Chatbots in Enhancing EFL Learners’Writing Macro Skills: Perceptions and Challenges - Eltom RahmtAllah, Enas Abdelwahab (Forum for Linguistic Studies, 2025)
This study investigates the perceptions and challenges experienced by Saudi English as a Foreign Language (EFL) learners when using AI-powered chatbots to enhance their writing macro skills. A three-part questionnaire was administered to 206 EFL students at Qassim University to explore their views on the usefulness, motivational impact, and difficulties associated with these tools. The findings indicate that students perceive AI chatbots as highly beneficial for improving organizational and structural aspects of writing, such as essay structure, paragraph transitions, and idea development. However, perceptions were more moderate regarding their effectiveness in enhancing deeper analytical elements like argument coherence and critical thinking. Furthermore, the results displayed that while chatbots serve as a motivational tool for task engagement, their capacity to foster intrinsic motivation for critical analysis was limited. Significant challenges identified include generic feedback, suggestions misaligned with intended style or structure, and concerns about over-reliance and the suppression of personal voice. Qualitative analysis emphasized these issues, disclosing fears of dependency, superficial feedback, and a potential loss of authorial voice. The study concludes that while AI chatbots are valuable supplementary tools for developing writing macro skills, their integration requires careful pedagogical design to address their limitations and ethical considerations. Educators are recommended to promote critical AI literacy and design activities that encourage students to evaluate and refine AI-generated suggestions, thereby making sure that these tools support rather than hinder the development of independent writing skills.